Therapeutic Effects of Methylprednisolone on Clinical Symptoms in COVID-19 Patients at Dr. R. Goeteng Taroenadibrata Hospital - Baroroh, Hanif Nasiatul; Hana, Rifa Khairunnisa; Ekowati, Heny (Universitas Padjadjaran, 2024)
COVID-19 is a respiratory syndrome disease in humans caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Until now, treatment for COVID-19 has not been found. This study aimed to observed a therapeutic effect of methylprednisolone in COVID-19 patients. Medical records of COVID-19 patients at Dr. R. Goeteng Taroenadibrata Purbalingga Hospital were collected retrospectively as part of this descriptive observational study from October 2020 to September 2021. Utilizing the Wilcoxon and Sign Test, a statistical analysis was conducted to determine the therapeutic effect of methylprednisolone on variables such as temperature, respiratory rate, oxygen saturation, cough, and shortness of breath. A total of 132 patients met the inclusion criteria, with 87 patients in mild severity, 22 patients with moderate severity, and 23 patients with severe severity. The clinical symptoms of cough, dyspnea, RR values, and SpO2 improved when methylprednisolone was given to mild COVID-19 patients receiving treatment at RSUD Dr. R. Goeteng Taroenadibrata Purbalingga. Additionally, clinical symptoms related to cough, SpO2, and temperature parameters improved in patients with moderate severity; in contrast, breathlessness, respiratory distress, SpO2, and temperature parameters improved in patients with severe severity. In conclusion, Goeteng Taroenadibrata Hospital COVID-19 patients report improved clinical symptoms when receiving methylprednisolone.